Formulasi Nanopartikel Zerumbon dari Rimpang Lempuyang Gajah (Zingiber zerumbet l.) : Enkapsulasi dengan Kitosan dan Aktivitas Sitotoksiknya terhadap Sel Kanker T47D - Andasari, Sholikhah Deti, Dr. Muhammad Da'i, M.Si., Apt (2017)
Zerumbone was the main compound of Zingiber zerumbet L. which has antioxidant and anticancer activities. It has low solubility in water because it was an one of essential oil group. The goal of this study was to formulate zerumbone-loaded chitosan nanoparticles in as a drug delivery system and to known their cytotoxic activity in T47D cells. Isolation of zerumbon was conducted by water and steam distillation to obtain essential oils. The oil was recrystallized using n-hexane. The crystals of zerumbone were analyzed by GC-MS qualitatively. Zerumbone was encapsulated in chitosan by ionic gelation method using Na-TPP as a cross linker agent in different concentration of chitosan. The activity of zerumbone nanoencapsulated in chitosan was conducted by MTT mrthod. Results showed that the prepared zerumbone nanoparticles had an average size in range from 280 to 680 nm and carried a positive charge with zeta potential from +10.9 to +38.3 mV. The entrapment efficiency of Zer-NPs were less than 2%. The zerumbone in nanoparticles showed lower cytotoxic activity againt T47D cells compared to pure zerumbone IC50 2196,5 and 7,57 µg/ml. Keywords: Chitosan, encapsulation, Na-TPP, zerumbone.